Bacterial Biofilms in Colorectal Cancer Initiation and Progression. Issue 1 (January 2017) - Li, Shan; Konstantinov, Sergey R.; Smits, Ron; Peppelenbosch, Maikel P.
Abstract : Intestinal microbiota have emerged as an important factor in colorectal cancer (CRC) initiation and progression. The currently prominent view on bacterial tumorigenesis is that CRC initiation is triggered by local mucosal colonization with specific pathogens (drivers), and that subsequent changes in the peritumoral environment allow colonization by opportunistic (passenger) microbes, further facilitating disease progression. Screening for CRC 'driver-passenger' microorganisms might thus allow early CRC diagnosis or preventive intervention. Such efforts are now being revolutionized by the notion that CRC initiation and progression require organization of bacterial communities into higher-order structures termed biofilms. We explore here the concept that a polymicrobial biofilm promotes pro-carcinogenic activities that may partially underlie progression along the adenoma–CRC axis. Trends: The organization of bacterial communities into biofilms (higher-order spatial structures of bacterial species) may be necessary for bacteria-induced CRC initiation. The interaction of the intestinal epithelium with the microbiota is highly dependent on the nature of the spatial organization of bacterial communities. Bacterial biofilms might act as direct triggering factors contributing to colorectal cancer. The biofilm confers highly-invasive properties to opportunistic bacteria, and a putative tumor-promoting potential. In experimental models, biofilm microbial populations can significantly impair the intestinal epithelial barrier function, alter polyamine metabolism affecting cellular proliferation, enhance proinflammatory/pro-oncogenic responses, and exacerbate intestinal dysbiosis. The invasive and co-aggregation capacity of microbiota may be essential for biofilm-promoted colon tumorigenesis.